Q1. The answer is
![4y+ \frac{1}{2y-1}](https://tex.z-dn.net/?f=4y%2B%20%5Cfrac%7B1%7D%7B2y-1%7D)
![\frac{8y^{2}-4y+1 }{2y-1} = \frac{4y*2y-4y+1}{2y-1} = \frac{4y(2y-1)+1}{2y-1} = \frac{4y(2y-1)}{2y-1}+ \frac{1}{2y-1} =4y+ \frac{1}{2y-1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B8y%5E%7B2%7D-4y%2B1%20%7D%7B2y-1%7D%20%3D%20%5Cfrac%7B4y%2A2y-4y%2B1%7D%7B2y-1%7D%20%3D%20%5Cfrac%7B4y%282y-1%29%2B1%7D%7B2y-1%7D%20%3D%20%5Cfrac%7B4y%282y-1%29%7D%7B2y-1%7D%2B%20%5Cfrac%7B1%7D%7B2y-1%7D%20%3D4y%2B%20%5Cfrac%7B1%7D%7B2y-1%7D)
Q2. The answer is
![2a+3+ \frac{6}{a-1}](https://tex.z-dn.net/?f=2a%2B3%2B%20%5Cfrac%7B6%7D%7Ba-1%7D)
![\frac{2 a^{2}+a+3 }{a-1} = \frac{a*2a-2a+3a+3}{a-1} = \frac{2a(a-1)+3a+3}{a-1}= \frac{2a(a-1)}{a-1}+ \frac{3a+3}{a-1} = \\ \\ =2a+ \frac{3a+3}{a-1}=2a+ \frac{3a-3+3+3}{a-1}=2a+ \frac{3(a-1)+6}{a-1} =2a+ \frac{3(a-1)}{a-1} + \frac{6}{a-1}= \\ \\ =2a+3+ \frac{6}{a-1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%20a%5E%7B2%7D%2Ba%2B3%20%7D%7Ba-1%7D%20%3D%20%5Cfrac%7Ba%2A2a-2a%2B3a%2B3%7D%7Ba-1%7D%20%3D%20%5Cfrac%7B2a%28a-1%29%2B3a%2B3%7D%7Ba-1%7D%3D%20%20%5Cfrac%7B2a%28a-1%29%7D%7Ba-1%7D%2B%20%5Cfrac%7B3a%2B3%7D%7Ba-1%7D%20%3D%20%5C%5C%20%20%5C%5C%20%3D2a%2B%20%5Cfrac%7B3a%2B3%7D%7Ba-1%7D%3D2a%2B%20%5Cfrac%7B3a-3%2B3%2B3%7D%7Ba-1%7D%3D2a%2B%20%5Cfrac%7B3%28a-1%29%2B6%7D%7Ba-1%7D%20%3D2a%2B%20%5Cfrac%7B3%28a-1%29%7D%7Ba-1%7D%20%2B%20%5Cfrac%7B6%7D%7Ba-1%7D%3D%20%5C%5C%20%20%5C%5C%20%3D2a%2B3%2B%20%5Cfrac%7B6%7D%7Ba-1%7D)
<span>
Q3. The answer is </span>
![2 x^{2} +5x+2](https://tex.z-dn.net/?f=2%20x%5E%7B2%7D%20%2B5x%2B2)
<span>
</span>
![\frac{6 x^{3} +11 x^{2} -4x-4}{3x-2} = \frac{3x*2 x^{2}-2 x^{2} *2+15 x^{2} -4x-4 }{3x-2} = \frac{2 x^{2} (3x-2)+15 x^{2} -4x-4}{3x-2}= \\ \\ = \frac{2 x^{2} (3x-2)}{3x-2} + \frac{15 x^{2} -4x-4}{3x-2} =2 x^{2} +\frac{15 x^{2} -4x-4}{3x-2}=2 x^{2} + \frac{15 x^{2} -10x+6x-4}{3x-2}= \\ \\ =2 x^{2} + \frac{5x*3x-5x*2+6x-4}{3x-2} =2 x^{2} + \frac{5x(3x-2)+3x*2-2*2}{3x-2} = \\ \\ =2 x^{2} + \frac{5x(3x-2)}{3x-2} + \frac{3x*2-2*2}{3x-2} =2 x^{2} +5x+ \frac{2(3x-2)}{3x-2} =2 x^{2} +5x+2](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%20x%5E%7B3%7D%20%2B11%20x%5E%7B2%7D%20-4x-4%7D%7B3x-2%7D%20%3D%20%5Cfrac%7B3x%2A2%20x%5E%7B2%7D-2%20x%5E%7B2%7D%20%2A2%2B15%20x%5E%7B2%7D%20-4x-4%20%20%7D%7B3x-2%7D%20%3D%20%5Cfrac%7B2%20x%5E%7B2%7D%20%283x-2%29%2B15%20x%5E%7B2%7D%20-4x-4%7D%7B3x-2%7D%3D%20%5C%5C%20%20%5C%5C%20%3D%20%20%5Cfrac%7B2%20x%5E%7B2%7D%20%283x-2%29%7D%7B3x-2%7D%20%2B%20%5Cfrac%7B15%20x%5E%7B2%7D%20-4x-4%7D%7B3x-2%7D%20%3D2%20x%5E%7B2%7D%20%2B%5Cfrac%7B15%20x%5E%7B2%7D%20-4x-4%7D%7B3x-2%7D%3D2%20x%5E%7B2%7D%20%2B%20%5Cfrac%7B15%20x%5E%7B2%7D%20-10x%2B6x-4%7D%7B3x-2%7D%3D%20%5C%5C%20%20%5C%5C%20%3D2%20x%5E%7B2%7D%20%2B%20%5Cfrac%7B5x%2A3x-5x%2A2%2B6x-4%7D%7B3x-2%7D%20%3D2%20x%5E%7B2%7D%20%2B%20%5Cfrac%7B5x%283x-2%29%2B3x%2A2-2%2A2%7D%7B3x-2%7D%20%3D%20%5C%5C%20%20%5C%5C%20%3D2%20x%5E%7B2%7D%20%2B%20%5Cfrac%7B5x%283x-2%29%7D%7B3x-2%7D%20%20%2B%20%5Cfrac%7B3x%2A2-2%2A2%7D%7B3x-2%7D%20%3D2%20x%5E%7B2%7D%20%2B5x%2B%20%5Cfrac%7B2%283x-2%29%7D%7B3x-2%7D%20%3D2%20x%5E%7B2%7D%20%2B5x%2B2)
<span>
Q4. The answer is 2x + 7
</span>
![\frac{6 x^{2} +11x-35}{3x-5} = \frac{6 x^{2} -10x+21x-35 }{3x-5} = \frac{3 x *2x-5*2x+7*3x-7*5 }{3x-5} = \\ \\ = \frac{2x(3x-5)+7(3x-5)}{3x-5}= = \frac{(3x-5)(2x+7)}{3x-5} =2x+7](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%20x%5E%7B2%7D%20%2B11x-35%7D%7B3x-5%7D%20%3D%20%5Cfrac%7B6%20x%5E%7B2%7D%20-10x%2B21x-35%20%7D%7B3x-5%7D%20%3D%20%20%5Cfrac%7B3%20x%20%2A2x-5%2A2x%2B7%2A3x-7%2A5%20%7D%7B3x-5%7D%20%3D%20%5C%5C%20%20%5C%5C%20%3D%20%5Cfrac%7B2x%283x-5%29%2B7%283x-5%29%7D%7B3x-5%7D%3D%20%3D%20%5Cfrac%7B%283x-5%29%282x%2B7%29%7D%7B3x-5%7D%20%3D2x%2B7)
<span>
Q5. The answer is </span>
![x+1- \frac{3}{x-1}](https://tex.z-dn.net/?f=x%2B1-%20%5Cfrac%7B3%7D%7Bx-1%7D)
<span>
</span>
![\frac{ x^{2} -4}{x-1} = \frac{ x^{2} -x+x-1-3 }{x-1} = \frac{x*x-x+x-1-3}{x-1} = \frac{x(x-1)+(x-1)-3}{x-1} = \\ \\ \frac{(x+1)(x-1)-3}{x-1} = \frac{(x+1)(x-1)}{x-1} -\frac{3}{x-1} =x+1- \frac{3}{x-1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20x%5E%7B2%7D%20-4%7D%7Bx-1%7D%20%3D%20%5Cfrac%7B%20x%5E%7B2%7D%20-x%2Bx-1-3%20%7D%7Bx-1%7D%20%3D%20%5Cfrac%7Bx%2Ax-x%2Bx-1-3%7D%7Bx-1%7D%20%3D%20%5Cfrac%7Bx%28x-1%29%2B%28x-1%29-3%7D%7Bx-1%7D%20%3D%20%20%5C%5C%20%20%5C%5C%20%5Cfrac%7B%28x%2B1%29%28x-1%29-3%7D%7Bx-1%7D%20%3D%20%20%5Cfrac%7B%28x%2B1%29%28x-1%29%7D%7Bx-1%7D%20%20-%5Cfrac%7B3%7D%7Bx-1%7D%20%3Dx%2B1-%20%5Cfrac%7B3%7D%7Bx-1%7D)
Q6. The answer is
![y^{2} -2y+3](https://tex.z-dn.net/?f=y%5E%7B2%7D%20-2y%2B3)
![\frac{ y^{3}-4 y^{2}+7y-6 }{y-2} = \frac{y* y^{2} -2y^{2}-2 y^{2} +7y-6 }{y-2} = \frac{y^{2}(y-2)-2 y^{2} +7y-6}{y-2}= \\ \\ = \frac{y^{2}(y-2)}{y-2}+ \frac{-2 y^{2} +7y-6}{y-2} = y^{2} + \frac{-2 y^{2} +4y + 3y-6}{y-2} = \\ \\ =y^{2} + \frac{-2y*y-2y(-2)+3y-3*2}{y-2} = y^{2} + \frac{(-2y)(y-2)+3(y-2)}{y-2} = \\ \\ = y^{2} + \frac{(-2y+3)(y-2)}{y-2} = y^{2} +(-2y+3) =y^{2} -2y+3](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20y%5E%7B3%7D-4%20y%5E%7B2%7D%2B7y-6%20%20%7D%7By-2%7D%20%3D%20%5Cfrac%7By%2A%20y%5E%7B2%7D%20-2y%5E%7B2%7D-2%20y%5E%7B2%7D%20%2B7y-6%20%7D%7By-2%7D%20%3D%20%5Cfrac%7By%5E%7B2%7D%28y-2%29-2%20y%5E%7B2%7D%20%2B7y-6%7D%7By-2%7D%3D%20%5C%5C%20%20%5C%5C%20%3D%20%5Cfrac%7By%5E%7B2%7D%28y-2%29%7D%7By-2%7D%2B%20%20%20%5Cfrac%7B-2%20y%5E%7B2%7D%20%2B7y-6%7D%7By-2%7D%20%3D%20y%5E%7B2%7D%20%2B%20%5Cfrac%7B-2%20y%5E%7B2%7D%20%2B4y%20%2B%203y-6%7D%7By-2%7D%20%3D%20%20%5C%5C%20%20%5C%5C%20%3Dy%5E%7B2%7D%20%2B%20%5Cfrac%7B-2y%2Ay-2y%28-2%29%2B3y-3%2A2%7D%7By-2%7D%20%3D%20y%5E%7B2%7D%20%2B%20%5Cfrac%7B%28-2y%29%28y-2%29%2B3%28y-2%29%7D%7By-2%7D%20%3D%20%5C%5C%20%20%5C%5C%20%3D%20y%5E%7B2%7D%20%2B%20%5Cfrac%7B%28-2y%2B3%29%28y-2%29%7D%7By-2%7D%20%3D%20y%5E%7B2%7D%20%2B%28-2y%2B3%29%20%3Dy%5E%7B2%7D%20-2y%2B3)
<span>
Q7. The answer is </span>
![x^{2} +xy+ y^{2}}{x-y}](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2Bxy%2B%20y%5E%7B2%7D%7D%7Bx-y%7D%20)
<span>
</span>
![\frac{ x^{3} - \frac{x}{y} y^{3} }{x-y} = \frac{(x-y)( x^{2} +xy+ y^{2}) }{x-y} = \frac{ x^{2} +xy+ y^{2}}{x-y}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20x%5E%7B3%7D%20-%20%5Cfrac%7Bx%7D%7By%7D%20%20y%5E%7B3%7D%20%7D%7Bx-y%7D%20%3D%20%20%5Cfrac%7B%28x-y%29%28%20x%5E%7B2%7D%20%2Bxy%2B%20y%5E%7B2%7D%29%20%7D%7Bx-y%7D%20%3D%20%5Cfrac%7B%20x%5E%7B2%7D%20%2Bxy%2B%20y%5E%7B2%7D%7D%7Bx-y%7D%20)
<span>
Q8. The answer is </span>
![(a^{2} +2ab+2b^{2})](https://tex.z-dn.net/?f=%28a%5E%7B2%7D%20%2B2ab%2B2b%5E%7B2%7D%29)
<span>
</span>
![\frac{a^{4} +4b^{4} }{a^{2}-2ab+2 b^{2} } = \frac{ (a^{2})^{2} +(2b)^{2}}{a^{2}-2ab+2 b^{2}} = \frac{(a^{2} -2ab+2b^{2})(a^{2} +2ab+2b^{2}) }{(a^{2} -2ab+2b^{2})} =(a^{2} +2ab+2b^{2})](https://tex.z-dn.net/?f=%20%5Cfrac%7Ba%5E%7B4%7D%20%2B4b%5E%7B4%7D%20%7D%7Ba%5E%7B2%7D-2ab%2B2%20b%5E%7B2%7D%20%7D%20%3D%20%5Cfrac%7B%20%28a%5E%7B2%7D%29%5E%7B2%7D%20%2B%282b%29%5E%7B2%7D%7D%7Ba%5E%7B2%7D-2ab%2B2%20b%5E%7B2%7D%7D%20%3D%20%5Cfrac%7B%28a%5E%7B2%7D%20-2ab%2B2b%5E%7B2%7D%29%28a%5E%7B2%7D%20%2B2ab%2B2b%5E%7B2%7D%29%20%7D%7B%28a%5E%7B2%7D%20-2ab%2B2b%5E%7B2%7D%29%7D%20%3D%28a%5E%7B2%7D%20%2B2ab%2B2b%5E%7B2%7D%29)
<span>
Q9. The answer is a^{n-8} - a^{-14}
</span>
Answer:
y= -7x-8
Step-by-step explanation:
The slope intercept form is y = mx + b.
First, find the slope. Use rise/run which gives you -7. <= negative bc its a negative slope.
Next, find the y intercept for b. It is -8.
Now, combine the numbers. y = -7x-8.
Leg * /2 = hypotenuse
Hypotenuse divided by /2 = leg
12 divided by /2
Rationalize denominator:
12 * /2 divided by by /2 * /2
Simplify denominator:
12 * /2 divided by 2
Simplify:
6 * /2 or 4.24
Both x and y because it’s a 45-45-90 triangle
Answer:
Step-by-step explanation:
so first you multiply how much she jogged then put the in infront of the number
The longer piece of wire is 42.5
The shorter piece of wire is 37.5
37.5+42.5=80
37.5 matches the requirements because it is 5 smaller than 42.5 :)
Mark as BRAINLIEST please :)